Sustainable ceramic membrane for decontamination of water: A cost-effective approach. Issue 2 (February 2023) - Latwal, Mamta; Arora, Shefali; Joshi, Abhishek; Irfan, Md; Pandey, Ganesh
Abstract: A sustainable ceramic membrane embedded with silver has been developed using quartz, kaolin and calcium carbonate. All the chemicals involved in this process were commonly available, non-toxic and cheap. The process was very simple, convenient and does not involve any wastage of water. Decoration of silver particles onto the porous ceramic membrane with the help of APTES as a connecting molecule leads to the formation of a durable material having strong antibacterial capacity. The fabricated membrane holds wide pore morphology with pore size of 4.4 μm and average porosity of 19.5% with an estimated cost of fabrication of about 60 dollar/m 2 . The membrane was found capable in reducing the TDS, BOD and COD of water samples that confirms that it is efficient for water treatment applications.